Effective field theory of magnetogenesis identify necessary and sufficient conditions. Issue 1 (1st January 2023) - Kushwaha, Ashu; Naskar, Abhishek; Nandi, Debottam; Shankaranarayanan, S.
Abstract: At astrophysical and cosmological scales, there is a detectable amount of magnetic field. There are several probable origins for this observed magnetic field, including the possibility of its origin in the early Universe. There are several models for primordial magnetogenesis, and if the inflationary background is taken into account, broken conformal invariance is required to generate a sufficient amount of magnetic field. The breaking of conformal invariance is introduced either by new couplings between electromagnetic field and inflaton field or including higher derivative terms to the theory. As a step to unify these different approaches in the literature, we propose an Effective Field Theory (EFT) approach based on expansion about the Hubble parameter ( H ) and its derivatives, where EFT parameters describe the magnetogenesis scenario in the early Universe, and different choices of parameters correspond to different models. We explicitly show that the generation of primordial magnetic fields requires two necessary conditions — conformal invariance breaking and causal propagation. While broken conformal invariance is a common requirement for primordial magnetogenesis, for the first time, we show that causal propagation is also a necessary condition. We confirm this by considering a specific model of primordial magnetogenesis.